Sex Differences in Behavioral Symptoms and the Levels of Circulating GFAP, Tau, and NfL in Patients With Traumatic Brain Injury - Sass, Dilorom; Guedes, Vivian A.; Smith, Ethan G.; Vorn, Rany; Devoto, Christina; Edwards, Katie A.; Mithani, Sara; Hentig, James; Lai, Chen; Wagner, Chelsea; Dunbar, Kerri; Hyde, David R.; et al. (Frontiers in Pharmacology, 2021)
Traumatic brain injury (TBI) affects millions of Americans each year and has been shown to disproportionately impact those subject to greater disparities in health. Female sex is one factor that has been associated with disparities in health outcomes, including in TBI, but sex differences in biomarker levels and behavioral outcomes after TBI are underexplored. The aim of this cross sectional study is to investigate the relationship between postconcussive, depression, and post-traumatic stress disorder (PTSD) symptoms, as well as health related quality of life (HRQOL), and the levels of glial fibrillary acidic protein (GFAP), total tau (t-tau), neurofilament light chain (NfL), and ubiquitin C-terminal hydrolase-L1 (UCH-L1). Behavioral outcomes were evaluated with the Neurobehavioral Symptom Inventory (NSI), Patient Health Questionnaire-9 (PHQ-9), PTSD Checklist- Civilian Version (PCL-C), short form (SF)-36, and plasma levels of total tau, GFAP, NfL, and UCHL-1 measured with the Simoa-HDX. We observed that females had significantly higher levels of GFAP and tau (ps<0.05), and higher PHQ-9 scores, NSI total scores, NSI- vestibular, NSI-somatosensory, NSI-affective sub-scale scores (ps <0.05)), than males. In addition, females had lower scores in HRQOL outcomes of role limitations due to emotional problems, vitality, emotional well-being, social functioning, and pain compared to males (ps<0.05). Correlation analysis showed positive associations between levels of tau and the NSI-total and NSI-cognitive sub-scale scores (ps<0.05) in females. No significant associations were found for NfL or GFAP with NSI scores. For female participants, negative correlations were observed between tau and NfL concentrations and the SF-36 physical function subscale (ps<0.05), as well as tau and the social function subscale (p<0.001), while GFAP levels positively correlated with role limitations due to emotional problems (p=0.004). No significant associations were observed in males. Our findings suggest that sex differences exist in TBI-related behavioral outcomes, as well as levels of biomarkers associated with brain injury, and that the relationship between biomarker levels and behavioral outcomes is more evident in females than males. Future studies are warranted to corroborate these results, and to determine the implications for prognosis and treatment. The identification of candidate TBI biomarkers may lead to development of individualized treatment guidelines.